2017
DOI: 10.1126/scitranslmed.aam5752
|View full text |Cite
|
Sign up to set email alerts
|

A multimechanistic antibody targeting the receptor binding site potently cross-protects against influenza B viruses

Abstract: Influenza B virus causes considerable disease burden worldwide annually, highlighting the limitations of current influenza vaccines and antiviral drugs. In recent years, broadly neutralizing antibodies (bnAbs) against hemagglutinin (HA) have emerged as a new approach for combating influenza. We describe the generation and characterization of a chimeric monoclonal antibody, C12G6, that cross-neutralizes representative viruses spanning the 76 years of influenza B antigenic evolution since 1940, including viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 32 publications
(47 reference statements)
1
79
0
1
Order By: Relevance
“…While a majority of these MAbs have neutralizing activity in vitro, broad protection conferred in vivo by nonneutralizing antibodies via Fc-Fc receptor interactions has been described as well (9)(10)(11). Data for broadly protective influenza B virus antibodies are sparse and limited to only a few studies reporting a small number of MAbs capable of displaying broad influenza B virus neutralization capacity in vitro (12)(13)(14)(15).…”
Section: Adcc Ha Influenza B Mabmentioning
confidence: 99%
“…While a majority of these MAbs have neutralizing activity in vitro, broad protection conferred in vivo by nonneutralizing antibodies via Fc-Fc receptor interactions has been described as well (9)(10)(11). Data for broadly protective influenza B virus antibodies are sparse and limited to only a few studies reporting a small number of MAbs capable of displaying broad influenza B virus neutralization capacity in vitro (12)(13)(14)(15).…”
Section: Adcc Ha Influenza B Mabmentioning
confidence: 99%
“…Although detection of viruses that exhibit reduced susceptibility to NA inhibitors or baloxavir marboxil in immunocompetent patients has frequently been reported 1,[4][5][6][7][8][9] , such viruses usually do not dominate susceptible viruses with the exception of the worldwide spread of oseltamivir-resistant H1N1 virus in the 2007-2008 season. Recently, broadly protective human monoclonal antibodies (mAbs) against conserved regions of HA, including the receptorbinding site (RBS) and stem region, have been evaluated [10][11][12][13][14][15][16] and studies for their clinical application are being conducted [17][18][19][20] . However, no human mAbs are currently available for clinical use.…”
mentioning
confidence: 99%
“…It is worth noting that neutralization and ADCC are not mutually exclusive. Antibodies with both anti-viral mechanisms have also been identified and characterized in recent studies, which demonstrated that ADCC activity could occur concurrently with a neutralization response [23,106]. Shen et al reported that one HA head-targeted antibody, C12G6, can not only neutralize Yamagata, Victoria and earlier lineages of influenza B viruses, but also inhibits the membrane fusion, virus egress, and induces an ADCC response [106].…”
Section: Hi-positive Head-targeting Mabs Cannot Mediate Robust Adcc Amentioning
confidence: 99%
“…Antibodies with both anti-viral mechanisms have also been identified and characterized in recent studies, which demonstrated that ADCC activity could occur concurrently with a neutralization response [23,106]. Shen et al reported that one HA head-targeted antibody, C12G6, can not only neutralize Yamagata, Victoria and earlier lineages of influenza B viruses, but also inhibits the membrane fusion, virus egress, and induces an ADCC response [106]. Notably, they also demonstrated that the potency of C12G6-mediated ADCC activity against different viruses followed an opposite trend to its HI activity, in which higher HI titer was found to be associated with relatively lower ADCC activity, and vice versa.…”
Section: Hi-positive Head-targeting Mabs Cannot Mediate Robust Adcc Amentioning
confidence: 99%